Molecular Biology in Plant Pathogenesis and Disease Management Microbial Plant Pathogens, Volume 1 - Narayanasamy, P. (Springer Netherlands : Imprint: Springer, 2008)
Studies on molecular biology of pathogens, infection process and disease resistance, have provided information essentially required to understand the vulnerable stages at which the pathogens can be tackled effectively and to adopt novel strategies to incorporate disease resistance genes from diverse sources and /or to induce resistance of cultivars with desirable agronomic attributes using biotic or abiotic agents. The nature of interaction between the gene products of the pathogen and plant appears to determine the outcome of the interaction resulting in either disease progression or suppression. Transgenic plants with engineered genes show promise for effective exploitation of this approach for practical application. Research efforts during the recent years to sequence the whole genomes of the pathogens and plants may lead to development of better ways of manipulating disease resistance mechanisms enabling the grower to achieve higher production levels and the consumer to enjoy safer food and agricultural products. Experimental protocols included in appropriate chapters will be useful for researchers and graduate students.